Lifetime Extension and Traffic Optimization in Wireless Sensor Networks Through Advanced Routing Algorithms - Mishra, Abhinav; K, Gopalakrishna; Acharya, Biswa Mohan; Ramesh, P. N.; Sriram, Siddharth; G, Kalanandhini (2025 2nd International Conference On Multidisciplinary Research and Innovations in Engineering (MRIE), 2025)
In the context of agricultural precision farming, wireless sensor networks (WSN) make it possible to regulate a variety of external variables and crop conditions. One kind of farm administration is precise farming, which involves the systematic collection, organisation, and analysis of information. Managing choices may be supported by integrating such data into other readily available knowledge. The goal is to maximise the efficiency, effectiveness, profits, and the long-term viability of farming operations by basing them on anticipated variation. Both the node lifespan and system reliability in WSN are quite short. Wireless sensor networks have an elevated energy usage rate due to their structure. Improving the lifespan of wireless networks necessitates developing an ideal structure that incorporates precise agriculture. One way to lengthen the life of a network is with the help of the OTELR routing approach, which is the subject of the current proposal. In order to include a node in the procedure for routing, we utilised Fuzzy Logic to determine its heuristic significance process. Utilising this technique, the weakest node may support the whole network lifetime, since it continues until all other nodes achieve its energy level, at which point it not take part in the routing procedure. Less energy is used in the suggested work in WSN via effective routing.